THE ROLE OF STRATEGIC CREATIVITY CAPABILITIES IN ENHANCING SUSTAINABLE COMPETITIVE ADVANTAGE-A SURVEY STUDY ON A SAMPLE OF PRIVATE BANKS IN BAGHDAD - Zahraa qais; Safaa J. Abdlhussin; Hafsa Atallah Hussein (Scholars Digest Publishing, 2024)
This study addressed the impact of strategic creativity capabilities with sustainable competitive advantage as a responsive variable through external marketing strategy. This study was launched from an intellectual dilemma with two dimensions, a theoretical dimension represented in the scarcity of writings that addressed the impact of strategic creativity capabilities on building sustainable competitive advantage, as strategic creativity capabilities and sustainable competitive advantage were not addressed by researchers, as well as how to determine the readiness of business organizations to work based on strategic creativity capabilities and explain their impact on building sustainable competitive advantage. The study aims to provide a theoretical framework for strategic creativity, and to try to test the Iraqi environment to embrace these modern concepts, and to find the relationship between building sustainable competitive advantage. The study method was a descriptive analytical method, and the study identified a set of hypotheses as temporary, speculative answers to the study problem, which were tested with non-parametric statistical tools. A random sample of (106) managers from senior, middle and supervisory management was selected in a sample of private Iraqi banks. The study concluded that strategic creativity capabilities improve in building sustainable competitive advantage for banks. This shows that the role of strategic creativity capabilities is distinctive in building sustainable competitive advantage. The study recommended the necessity of investing in strategic creativity capabilities in achieving sustainable competitive advantage, encouraging Iraqi private banks to build flexible organizational structures, linking reward policies and development programs with existing skills and granting them on a collective basis, and the necessity of using modern technology and adopting an advanced system.
Keywords: Strategic innovation capabilities, sustainable competitive advantage, organizational characteristics, supply chain characteristics, strategic learning mechanisms for dynamic capabilities, private banks